A New Brachylophosaurin Hadrosaur (Dinosauria: Ornithischia) with an Intermediate Nasal Crest from the Campanian Judith River Formation of Northcentral Montana. - Elizabeth A Freedman Fowler; John R Horner (PLoS ONE, 2015)
Brachylophosaurini is a clade of hadrosaurine dinosaurs currently known from the Campanian (Late Cretaceous) of North America. Its members include: Acristavus gagslarsoni, which lacks a nasal crest; Brachylophosaurus canadensis, which possesses a flat paddle-shaped nasal crest projecting posteriorly over the dorsal skull roof; and Maiasaura peeblesorum, which possesses a dorsally-projecting nasofrontal crest. Acristavus, from the lower Two Medicine Formation of Montana (~81-80 Ma), is hypothesized to be the ancestral member of the clade. Brachylophosaurus specimens are from the middle Oldman Formation of Alberta and equivalent beds in the Judith River Formation of Montana; the upper Oldman Formation is dated 77.8 Ma.A new brachylophosaurin hadrosaur, Probrachylophosaurus bergei (gen. et sp. nov.) is described and phylogenetically analyzed based on the skull and postcranium of a large individual from the Judith River Formation of northcentral Montana (79.8-79.5 Ma); the horizon is equivalent to the lower Oldman Formation of Alberta. Cranial morphology of Probrachylophosaurus, most notably the nasal crest, is intermediate between Acristavus and Brachylophosaurus. In Brachylophosaurus, the nasal crest lengthens and flattens ontogenetically, covering the supratemporal fenestrae in large adults. The smaller nasal crest of Probrachylophosaurus is strongly triangular in cross section and only minimally overhangs the supratemporal fenestrae, similar to an ontogenetically earlier stage of Brachylophosaurus. Sutural fusion and tibial osteohistology reveal that the holotype of Probrachylophosaurus was relatively more mature than a similarly large Brachylophosaurus specimen; thus, Probrachylophosaurus is not simply an immature Brachylophosaurus.The small triangular posteriorly oriented nasal crest of Probrachylophosaurus is proposed to represent a transitional nasal morphology between that of a non-crested ancestor such as Acristavus and the large flat posteriorly oriented nasal crest of adult Brachylophosaurus. Because Probrachylophosaurus is stratigraphically and morphologically intermediate between these taxa, Probrachylophosaurus is hypothesized to be an intermediate member of the Acristavus-Brachylophosaurus evolutionary lineage.